The Design and Printing of Bank Notes : Considerations When Introducing a New Currency - Abrams, Richard (IMF Working Papers; Working Paper, 1995)
Many newly independent or systemically transforming countries feel a pressing need to--or must--introduce their own national currency. Other countries simply wish to enhance the attractiveness, usefulness, durability, and/or security of their currencies. However, it is difficult to find consistent published information on the various aspects of this process. This paper attempts to ameliorate this problem by discussing the main issues in designing, producing, and printing a new currency, in order to help those charged with these tasks to proceed in an orderly and informed manner. Attention is also given to examining the options that may be available when this exercise must be undertaken on an emergency basis, with little or no warning.